Layered P2-Na2/3Co1/2Ti1/2O2 as a high-performance cathode material for sodium-ion batteries - Sabi, Noha; Doubaji, Siham; Hashimoto, Kazuki; Komaba, Shinichi; Amine, Khalil; Solhy, Abderrahim; Manoun, Bouchaib; Bilal, Essaid; Saadoune, Ismael (Journal of Power Sources, 2017)
Layered oxides are regarded as promising cathode materials for sodium-ion batteries. We present Na2/3Co1/2Ti1/2O2 as a potential new cathode material for sodium-ion batteries. The crystal features and morphology of the pristine powder were characterized by X-ray diffraction (XRD) and scanning electron microscopy (SEM). The cathode material is evaluated in galvanostatic charge-discharge and galvanostatic intermittent titration tests, as well as ex-situ X-ray diffraction analysis. Synthesized by a high-temperature solid state reaction, Na2/3Co1/2Ti1/2O2 crystallizes in P2-type structure with P63/mmc space group. The material presents reversible electrochemical behavior and delivers a specific discharge capacity of 100 mAh g−1 when tested in Na half cells between 2.0 and 4.2 V (vs. Na+/Na), with capacity retention of 98% after 50 cycles. Furthermore, the electrochemical cycling of this titanium-containing material evidenced a reduction of the potential jumps recorded in the NaxCoO2 parent phase, revealing a positive impact of Ti substitution for Co. The ex-situ XRD measurements confirmed the reversibility and stability of the material. No structural changes were observed in the XRD patterns, and the P2-type structure was stable during the charge/discharge process between 2.0 and 4.2 V vs. Na+/Na. These outcomes will contribute to the progress of developing low cost electrode materials for sodium-ion batteries. [Display omitted] •A positive electrode material based on Co and Ti for Na-ion batteries was prepared.•Na2/3Co1/2Ti1/2O2 crystallizes in P2-type structure with P63/mmc space group.•A specific discharge capacity of 100 mAh g−1 was obtained.•Na2/3Co1/2Ti1/2O2 shows better stability than Na2/3CoO2 (Cap. Ret. 98%).•Ex-situ XRD confirms the structural stability of the studied material upon cycling.